Functional evolution in total knee arthroplasty: first and second-generation patient-specific instrumentation compared with conventional instrumentation - Fontes, Ana Paula; Rui Miguel Cintra; Luís Gomes; João Paulo Sousa (International Journal of Research in Medical Sciences, 2023)
Background: This study compares the functional evolution between the first- and second-generation patient-specific instrumentation and conventional instrumentation pre-surgery and the third month post-surgery after TKA. We analyzed the functional outcomes achieved and the absolute gains of each study variable. In addition, we aimed to elucidate the results of the three surgical techniques regarding the surgery length of time, length of hospital stay, percentage drop in hemoglobin (Hg) at 24 h, and hip-knee-ankle angle post-surgery. Methods: We reported our experience in TKA using PSI Visionaire System® and CI technique in 688 procedures. The patients were divided into first (N=272) and second-generation (N=151) PSI designs. The control group (N=265) underwent TKA with the CI. The instruments for assessing the functioning were: visual analog scale, goniometry, 6-minute walk test (6MWT), and domains of the WOMAC Index. Results: The functioning achieved three months after surgery was lower in the CI than the first-generation PSI. The respective differences at absolute gains were found in the 6MWT and pain and function WOMAC scores (p=0.023, p=0.049, and p=0.018, respectively). The mean surgical time was higher in the CI compared to PSI designs (both p<0.001), and the mean hospital length of stay was higher in the CI compared to second-generation PSI (p=0.002). The percentual drop in Hg was higher in the first-generation PSI than with the CI (p=0.006). Conclusions: Three months after TKA, the functioning achieved with the first-generation PSI was greater than the CI. However, the functional results between second-generation PSI and CI were similar.